Perception of creative accounting: gap analysis solution among auditors and accountants in Bangladesh - Asif, Mahbub Karim (2016)
Creative Accounting is the practice that accountants and auditors may do in order to provide a rosy picture of the financial statements but of course keeping within the parameter of the accounting rules and regulations as laid down by International Accounting Standard , Bangladesh Accounting Standard or even Generally Accepted Accounting principles. The inception of creative accounting practice can be traced back to the times of Luca Pasioli when the double entries of the book keeping system emerged and even beyond that. The main purpose of the study was to investigate the perception of the accountants and auditors towards the application of creative accounting practices. Both primary and secondary data were collected and the mixed-methods were employed. The research was carried out by preparing a structured questionnaire. The questionnaire had five components. Components encompassed spheres like is creative accounting a blessing or a curse , the techniques applied to practice creative accounting, the application of creative accounting , the effects of creative accounting and finally the solution of creative accounting. The questionnaire was a closed ended structured question and made on 5 point likert scale. The main finding of the research was that creative accounting techniques applied in the financial statements was due to the fact that International Accounting Standards (IAS), Generally Accepted Accounting Principles (GAAP) or even International Financial Reporting Standard(s) (IFRS) guidelines regarding accounting policy for financial statement disclosures have its own limitation in certain areas. The implication of the research was to recommend preventive measures of such practices in the financial statements.